Adaptive Learning Platforms and Their Influence on Higher Education: A Scoping Review - Núñez Hernández, Corina; Avilés-Castillo, Fátima; Buele, Jorge (My University, 2025)
Over the past decade, adaptive learning platforms have transformed higher education by adjusting content and activities based on students’ abilities and progress. This approach personalizes learning and optimizes academic performance, particularly in complex disciplines such as engineering and science. However, challenges remain related to their technological implementation and acceptance by both students and educators. This scoping review analyzes the impact of adaptive learning platforms in higher education, focusing on their influence on academic performance, student motivation, practical implementation challenges, and future implications for research. An exploratory literature review was conducted using the PRISMA-ScR method, identifying recent studies published between 2019 and 2024 in databases such as ERIC, Scopus, IEEE Xplore, Web of Science, and APA PsycNet. Quantitative and qualitative research studies were selected, evaluating the impact of these platforms in university settings and the outcomes they produce. The results indicate that adaptive learning platforms significantly enhance academic performance by providing personalized experiences and immediate feedback. They also increase student motivation and engagement, particularly in online learning environments. However, challenges were identified, including the need for adequate technological infrastructure and specialized training for educators. Adaptive learning platforms hold transformative potential in higher education but require overcoming technological and pedagogical barriers. Further qualitative research is recommended to better understand user experiences and maximize their effectiveness across diverse educational contexts.
Keywords: Adaptive Learning; Educational Platforms; Educational Technologies; Higher Education; Personalized Learning